Developing a metacognitive thinking level scale for female futsal players - Fattah, Kamyar Mahmoud; Asaad, Asst. Prof. Dr. Diyar Kamal (Sulaimani Journal for Humanities, 2026)
The research aims to develop a scale for measuring metacognitive thinking levels among female futsal players. The research population was defined as (149) female futsal players from clubs in the Kurdistan Region of Iraq, of whom (139) were selected as the construct sample after excluding the (10) players who participated in the pilot study. The researchers reached a number of conclusions and recommendations.